(untitled) (Physical Education, Health and Social Sciences, 2025)
Background: A hormonal condition known as polycystic ovary syndrome (PCOS) affects many women of reproductive age. It is characterized by excessive levels of androgens, irregular menstruation periods, and ovarian cysts (male hormones). Due to high amounts of androgen hormones and women have trouble becoming pregnant (infertility). Worldwide, polycystic ovarian syndrome is on the rise, although most women are still ignorant of it. Objectives: The goal of the study and the accompanying data collection is to get a sense of the existing body of information and the frequency of polycystic ovarian syndrome symptoms in females. Methods: Two significant public universities, as well as several Quetta residential neighborhoods, were the subject of a mixed methods approach. Results: According to statistics, 24% of the 157 female students at the University of Balochistan in Quetta who are female have knowledge about polycystic ovarian syndrome. Only 25% of the 144 female respondents from Sardar Bahadir Khan University in Quetta said that they were aware of polycystic ovarian syndrome. In addition, albeit just 4%, this equates to 24 out of 79 females in residential areas knowing enough about polycystic ovarian syndrome. 45% of participants are unaware of polycystic ovarian syndrome. Conclusions: This study found that although the prevalence of Polycystic Ovarian Syndrome, signs, and symptoms is increasing in Quetta, many women are still ignorant of the disorder, without a significant or life-threatening illness or condition, the majority of women do not visit a gynaecologist. Moreover, they also have behavioral effects of Polycystic ovarian syndrome. It also exposes that polycystic ovarian syndrome has significant behavioural consequences on females that they are unaware of.